The Listening Comprehension of SMK Students in Demak - Atik Muji Rahayu (Magister Scientiae, 2013)
Listening is a language skill that assists the students to comprehend spoken language. However, listening is often neglected at schools in Indonesia due to the system of school curriculum in which listening to oral English is the skill least taught at school. As a result, listening becomes a difficult language skill for the students, especially vocational school students. There are many factors that students have to cope with in order to comprehend spoken English. To achieve a certain level of listening comprehension, students have to master micro and macro skills as mentioned in Brown’s taxonomy in listening comprehension. This study proved that there were four major factors that hindered students’ ability in listening comprehension: sounds, vocabulary, grammatical awareness and pragmatic differences. It was concluded that the main cause of the students’ inability to comprehend spoken language was micro skills, which happened to the students at low level, especially recognition of word sounds. Accordingly, micro skills should be introduced to enrich students’ knowledge of language.